Roses Fitness Services / Nur Hidayah Rose Azman Shah - Rose Azman, Nur Hidayah (2021)
Roses fitness services is an organization that ensures that individuals embark on strong wellness and lifestyle goals in an educated and safe climate. We will be in Putrajaya precinct 19. We also provide online services that is virtually. The office for our recreation center will cater to local area health enthusiasts such as youngsters and guests. Our office will be equipped with the best class Rogue Fitness equipment from experienced trainers in addition to many other needs we provide coaching services for those in need. One of our important objectives for starting Roses fitness service is to encourage individuals to develop a tendency to exercise consistently and stay healthy. Our training center office is explicitly designed and works for individuals who are interested in embracing the CrossFit lifestyle and ways to practice a healthy lifestyle. Our participation groups are very diverse for individuals with a variety of objectives available at our training centers. We will continue to strive to ensure that we offer exceptional assistance and build relationships that help make the trend continue. Roses fitness service will transform into a premier CrossFit design center in a good area, we will strive to make our business successful to coordinate with our individual needs. Roses fitness service will be open 7.30 am-12 am seven days a week, for us to have the option to oblige individuals with various time tendencies. We have decided to enroll sufficient specialists and conduct employee exchanges among our workforces. We will make special efforts to procure standard preparation equipment for our training center. We will be running a health club that will help individuals who need to be more fit to fulfill their desires without the slightest bit of stress. We have a weight loss board specialist who will work with people who rely on wellness needs and altered diets